Melatih Motorik Halus Anak Melalui Kegiatan Meronce Studi Kasus Lembaga Pendidikan Islam di Aceh Tengah - Sapii, Muhammad; Isnawati, Isnawati (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
The formulation of the problem in this study is How are the steps in training fine motor skills and can using meronce train children's fine motor skills in Raudhatul Athfal Aceh Tengah? The purpose of this research is to find out the steps in practicing fine motor skills and to find out whether meronce can train fine motor skills for children in Raudhatul Athfal, Central Aceh. The research approach used is classroom action research (CAR). Classroom action research is a form of relative research conducted by the collaborators themselves, the results of which can be used as a tool for development. The research approach used in classroom action research is collaboration with the class teacher, Mrs. Khaira Ismi in Raudhatul Athfal, Central Aceh district. The results of classroom action research (CAR) in Raudhatul Athfal Aceh Tengah are: a) The steps used to train children's fine motor skills can use beading activities, namely by holding the needle correctly, inserting the thread into the needle carefully and carefully. Carefully then thread the bead into the thread through the needle. Furthermore, the beads are arranged according to the decorative objects desired by the child. b) from cycle I to cycle II, child development increased by 27%. Meanwhile, from pre-action to cycle II, there was an increase of 69%. The analysis above shows that the percentage of children's completeness from pre-action to cycle II has reached 90%. For this reason, the results of observations and evaluations have increased significantly.